2013
DOI: 10.1002/grl.50956
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil moisture‐climate feedbacks on CMIP5 projections: First results from the GLACE‐CMIP5 experiment

Abstract: [1] The Global Land-Atmosphere Climate ExperimentCoupled Model Intercomparison Project phase 5 (GLACE-CMIP5) is a multimodel experiment investigating the impact of soil moisture-climate feedbacks in CMIP5 projections. We present here first GLACE-CMIP5 results based on five Earth System Models, focusing on impacts of projected changes in regional soil moisture dryness (mostly increases) on late 21st century climate. Projected soil moisture changes substantially impact climate in several regions in both boreal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
348
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 356 publications
(366 citation statements)
references
References 35 publications
17
348
1
Order By: Relevance
“…They concluded that the potential changes in ET would be better described by GCMs than "off-line" PET models (such as the two models used in this study), as GCMs can explicitly consider more complex atmospheric processes, such as the interaction between CO 2 and stomatal conductance. Nevertheless, it should be noted that the current reliability of GCMs in simulating ET is also questionable, due to the uncertainty in representing soil moisture and radiative energy at the evaporative surface (e.g., Seneviratne et al, 2013;Boé and Terray, 2008;Barella-Ortiz et al, 2013). In addition, due to the coarse scale of GCM output, downscaling is generally required to post-process output for use at local and regional scales, which often adds further bias and uncertainties to the GCM simulation and largely limits their applicability (e.g., Chen et al, 2012;Diaz-Nieto and Wilby, 2005).…”
Section: Analyses Of Pet Sensitivitymentioning
confidence: 99%
“…They concluded that the potential changes in ET would be better described by GCMs than "off-line" PET models (such as the two models used in this study), as GCMs can explicitly consider more complex atmospheric processes, such as the interaction between CO 2 and stomatal conductance. Nevertheless, it should be noted that the current reliability of GCMs in simulating ET is also questionable, due to the uncertainty in representing soil moisture and radiative energy at the evaporative surface (e.g., Seneviratne et al, 2013;Boé and Terray, 2008;Barella-Ortiz et al, 2013). In addition, due to the coarse scale of GCM output, downscaling is generally required to post-process output for use at local and regional scales, which often adds further bias and uncertainties to the GCM simulation and largely limits their applicability (e.g., Chen et al, 2012;Diaz-Nieto and Wilby, 2005).…”
Section: Analyses Of Pet Sensitivitymentioning
confidence: 99%
“…They also found that improved simulation of solar radiation and precipitation leads to more accurate soil moisture simulations. Although the CMIP5 models have been used to investigate land-atmosphere interactions (Dirmeyer et al, 2013;Seneviratne et al, 2013;May et al, 2015;Lorenz et al, 2016), to date, there has not been a comprehensive evaluation of the accuracy of the CMIP5 soil moisture simulations in the United States. Therefore, this paper will address this knowledge gap.…”
Section: Introductionmentioning
confidence: 99%
“…An axis of analysis that has not been investigated in great detail is how a particular model's regional land-atmosphere coupling strength signature (Guo et al, 2006;Koster et al, 2004;Seneviratne et al, 2010Seneviratne et al, , 2013) affects simulations of the climate impact of land-use change. One can hypothesize that LULCC in a region where the land is tightly coupled to the atmosphere, generally due to the presence of a soil moisture-limited evapotranspiration regime (Koster et al, 2004;Seneviratne et al, 2010), will result in a stronger climate response than the same LULCC in a region where the atmosphere is not sensitive to land conditions.…”
Section: Radiative Forcingmentioning
confidence: 99%